Abstraction of underlying technology and domain management in development frameworks: a systematic literature review - Simoncini, Nicolás (2025)
Both software development companies and companies that implement in-house their applications usually focus the design of their software products using various development frameworks that facilitate “out of the box” the rapid implementation of functional requirements aimed at specific niches as is the case with Web applications, but they often lose focus on the correct management of the backend regarding to the management of application domains and the encapsulation and abstraction of the underlying technologies (that is, not providing tools or mechanisms of design to facilitate such abstraction). The present work aims to analyze, through a systematic literature review, the existence of academic research that results in valid methodologies or protocols for the modeling of frameworks oriented to the design of backends that allow the encapsulation and abstraction of the underlying technology and make use of ontologically valid application domains.